Effectivity of Dry and Liquid BS4 Enzymes in Improving Performance of Broiler Chickens Fed Different Nutrient Density Diet - Arnold Parlindungan Sinurat; Tuti Haryati; Nurul Pratiwi; Tresnawati Purwadaria (Indonesian Center for Animal Research and Development (ICARD), 2022)
Supplementation of enzymes in feed is now commonly practiced to increase the nutrient availability of feed and the performance of poultry. A new enzyme called BS4 was produced by cultivating Eupenicilium javanicum. It is necessary to test the efficacy of this enzyme since the effectiveness of enzyme supplementation depends on many factors. An experiment was conducted to study the effect of dietary BS4 enzyme supplementation in improving the performance of broiler chickens. A number of 300 broilers DOC was distributed into 30 pens and reared until 35 d. Six experimental diets i.e., factorial of 2 (Standard diet, and low nutrient density diet) X 3 (Control, BS4 liquid enzyme, and BS4 powder enzyme) were formulated with 5 replications. The performance (feed intake, body weight, FCR, and survival rates) were observed during the starter (1-21 d) and whole (1-35 d) periods. At the end of the trial, measurements were also made on the carcass yield, abdominal fat, liver, and gizzard weights. Results showed that performances of broilers from 1-35 d were not significantly affected by interaction between nutrient density and enzyme supplement. The nutrient density also did not affect performances of broilers. However, dietary enzyme supplementation significantly reduced feed intake and improved FCR of broilers as compared to the control. Supplementation of BS4 in liquid or powder form, reduced feed intake by 3.6%. Supplementation of liquid and powder BS4 enzymes improved FCR by 6.4% and 8.9%, respectively, but no different effect between liquid and powder BS4 enzymes on performance of broilers. Nutrient density, enzyme supplementation, and interactions between the two factors did not significantly influence carcass yield, abdominal fat, liver, and gizzard relative weights of broilers.